An Innovative Technique For Treating Severe Caries In Primary Teeth With Ozone: A Retrospective Investigation (Journal of Pharmaceutical Negative Results, 2023)
This research was planned to learn more about ozone treatment, a relatively new method for dealing with severe cases of primary tooth caries.Thirty-five children (sixteen girls and nineteen boys, aged 3 to 6) who had all had fillings from the same dentist were selected. Fifty-two were chosen for the repair process. After 3, 6, and 12 months, we asked a second operator to assess the success or failure of each restoration. The success rate at 12 months was 92.7 percent (n = 48 out of 52 restorations).In Conclusion, the extent of the carious lesions in the deciduous teeth included in this research meant that pulpotomy would have been necessary if the teeth had been treated traditionally. The suggested approach using ozone was shown to be an effective alternative, with the primary benefit of protecting tooth pulp and tissue against invasion.